MODEL PEMBELAJARAN SNOWBALL THOWING MEMPENGARUHI HASIL BELAJAR SISWA - Aliya Ariyanti, Siti; Aisah, Siti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The purpose of this study is to compare class IV students' learning outcomes before and after the snowball tossing learning approach was put into practice. This study uses an experimental design and quantitative methodology, with a single class serving as the research topic. Thirty students were enrolled at SDN Tapos 04 at the time of this research, and all of them served as samples. The pretest, posttest, and documentation methods were used in this study's data gathering. Both inferential statistical analysis and descriptive statistical methods were used in the analysis. The One Sample Kolmogorov-Smirnov Test was used to test the hypothesis, and SPSS Version 25 software was used to test the results using the Paired Samples Test. The hypothesis test employing the Paired Samples t test yielded a Sig. (2-tailed) of 0.000<0.05 based on the computation results. It has been demonstrated that using the snowball tossing learning approach significantly affects the learning objectives of students in class IV. In summary, HO is disproved and the Ha hypothesis is accepted